Equilibrium selection in an environmental growth model with a S-shaped production function. (January 2020) - Bella, Giovanni; Liuzzi, Danilo; Mattana, Paolo; Venturi, Beatrice
Abstract: This paper presents a purely dynamic economic-environmental growth model with a S -shaped production function and a pollution externality. We first outline the role of the saving rate in inducing/suppressing a dual steady-state, one with lower capital and pollution (the "green" steady state) than the other (the "dirty" steady state). Assuming the saving rate is such that the economy possesses a dual steady state, the second part of the paper exploits global analysis tecniques to study conditions such that the economy is able to escape the dirty steady state and approach the green steady state.